SURGICAL MANAGEMENT OF VULNUS LACERATUM ON THE BACK OF A DOG - I Gusti Ngurah Putu Krisnu Mahaputra; I Wayan Gorda; I Wayan Wirata (Buletin Veteriner Udayana, 2025)
Vulnus laceratum is a lacerated wound characterized by minimal tissue loss, typically resulting from trauma. A 6-month-old dog weighing 6 kg presented with a relatively large laceration on its back. Clinically, the dog remained active with a normal appetite and drinking behavior. Based on physical examination, the dog was diagnosed with vulnus laceratum on the dorsal region and given a favorable prognosis. The wound was treated surgically, beginning with thorough irrigation using physiological saline (NaCl), followed by debridement to remove necrotic and damaged tissue, thereby facilitating the healing process. The wound was then closed with sutures. Postoperative therapy included oral administration of cefadroxil (antibiotic), intramuscular tolfedine (anti-inflammatory), and topical gentamicin to prevent secondary infection. By the fifth postoperative day, the wound showed significant improvement and had begun to dry. The dog exhibited signs of clinical recovery and resumed normal activity.